Cutting in the Quran Morphological, syntactical and Semantical study - عصام إسماعيل الزيدي أنفال (Al-Adab Journal, 2018)
The study was initiated in the search for the word (cut) and derivatives that were mentioned in the Quran and the evacuation of meanings and connotations contained therein, it has widened its implications and included many other meanings is its true meaning. The study curriculum collect Quranic verses incorporating these word and incorporated under the semantics contained and revenue linguistic meaning of this word and then illustrate its meaning, according to the Quranic context, and to highlight morphological and grammatical aspects related by reflecting the views of linguists, scholars and grammarians and persuasions.